(untitled) (Sahel Journal of Life Sciences FUDMA, 2026)
Malaria is one of the most important public health challenges in sub-Saharan Africa. This study aimed to assess asymptomatic malaria in relation to the sociodemographic as well as the risk factors exposing the adolescents attending secondary schools in Ardo-Kola and Jalingo Local Government Areas, Taraba State, to malaria infection. A total of two hundred and eighty-six (286) samples were collected from adolescents attending secondary schools within the selected LGAs. Four schools were selected and equal samples were collected from each school to obtain the required sample size. All the samples were screened for malaria parasitaemia using microscopy and molecular techniques. The findings of this study revealed a prevalence of 13.9% (40/286) among the adolescents. In relation to age, infection was significantly higher, 22.7% (15/66), among those between 12-16 years old (χ² = 15.879, p = 0.053). Keeping of opened containers of water around the house significantly exposed the adolescents to malaria infection in Ardo-Kola and Jalingo Local Government Areas of Taraba state, Nigeria, with an adjusted odds ratio (aOR) of 5.09 (95% CI: 1.20-7.98, p=0.015). The findings indicate that despite ongoing malaria control efforts, silent transmission persists within the understudied age group, contributing to continuous malaria transmission in the urban and rural communities.